Turkey's Struggle with Internet in its 3rd year: Don Quixote, Ostrich, Harakiri - Mustafa Akgül (Türk Kütüphaneciliği)
The Code 5651 which sets Internet censhorship in Turkey has been active for 3 years. With this lawr, our country twanted to be a leader among democratic countries, , and challenged giant companies like Youtube and Google and fined them with tax penalty. Our country t is trying to set International Law on Internet via code 5651 and decisions of its courts. But it doesn't do this by defending or negotiating the issue on international forums or United Nations. It considers Internet as media and it punishes and bans similar to printing press.. A serious number of people, including the Prime Minister, break the ban. The President of the Republic, State Minister for EU, Minister of Transportation and chairman of Information and Communication Technologies Authority give statements against these bans. In the meantime, rule of law, separation of powers, fair trial, and basic human rights such as freedom of expression are ignored. In other words, a Legal Tradegy occurs in front of lawyers and intellectuals. And our country commits hara-kiri by not understanding Internet, just like the situation in printing machine. In this article, various dimensions of the 3-year struggle of Turkey with Internet are discussed.